POLISH STEREOLOGY – A HISTORICAL REVIEW - Gądek-Moszczak, Aneta; Matusiewicz, Piotr (Image Analysis and Stereology, 2017)
In the paper, the authors present the history of stereology development in Poland from the 1930s until now. The authors concentrate on the talented scholars whose hard work, dedication, and enthusiasm contributed to popularizing stereological methods of quantitative assessment. From Hugo Steinhaus to now, the evolution and increase in popularity of stereology is briefly shown. The most significant achievements are described in more detail.